Peran Kepemimpinan Transformasional dalam Meningkatkan Kinerja Perusahaan Asuransi - Siahaan, Trioksa; Setiadi, Edy; Siregar, Mulya Efendi; Harini, Hegar; Lanuharsa, Gerhad (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study attempts to examine the role of transformational leadership in optimizing insurance company performance. Transformational leadership is recognized for its capacity to inspire and encourage individuals to achieve organizational goals, bring about positive shifts, and improve operational efficiency and customer satisfaction. Employing a systematic literature review technique, this study gathered data from 10 papers on transformational leadership in insurance businesses published between 2020 and 2025 utilizing the Sinta database. The study's findings show that leaders who use a transformational leadership style might improve performance directly and indirectly. Furthermore, this study reveals several traits shared by transformational leaders to motivate endeavours to improve performance in insurance institutions. The study's findings imply that insurance companies ought to prioritize developing transformational leadership to increase their competitiveness and sustainability in a highly competitive industry. The study additionally proposes recommendations for incorporating leadership training and technological adoption into employee development strategies. Keywords: Transformational Leadership, Employee Performance, Insurance Companies